The indigenous consultation of investment projects within the Chilean Environmental Impact Assessment System: Background and results after a decade of Decree 66/2013 - Silva Valenzuela, Nicolás; Jara Villalobos, Camilo Andrés (Revista de Derecho Ambiental, 2023)
A central element of ILO Convention 169 is the obligation for States to consult with indigenous peoples on legal and administrative measures likely to affect them to achieve agreement or consent on such measures. Chile ratified Convention 169 in 2008 and regulated Indigenous Consultation of investment projects in the Environmental Impact Assessment System through Supreme Decrees N° 40/2012 and N° 66/2013. The literature has criticized the alleged lack of results of the mechanism for indigenous communities, that the consultation is not binding for the outcome of the environmental assessment, and the effective duration of the consultation procedures. Using official data from the Environmental Assessment Service, it has been estimated that 72.3% of consultations have ended in agreements with indigenous communities regarding investment projects. Although the outcome of the consultation is not legally binding for the environmental assessment, obtaining full agreement in the consultation is associated in 90.5% of the cases with obtaining a favorable Environmental Qualification Resolution for the project. The average duration of consultations is 22 months, five times the period established in DS 66/2013.